ANALISIS PENGARUH ANTAR KOMPONEN INTELLECTUAL CAPITAL TERHADAP GOODWILL PADA PT ADIRA DINAMIKA MULTI FINANCE TBK PERIODE 2013-2018 - Anggraeni, Lisda; Ghalib, Saladin (Bisnis Smart, 2020)
The purpose of this study to analyze the effect of Human Capital (X1), Capital Employed (Z1), Structural Capital (Z2) on Goodwill (Y), and the influence between intellectual capital components in PT Adira Dinamika Multi Finance Tbk Period 2013-2018. Data source is secondary data analysis using Partial Least Square (PLS). The results showed that Human Capital (X1) and Capital Employed (Z1) significantly and positive influence on Goodwill(Y). While Structural Capital (Z2) has a significant and negative effect on Goodwill (Y). With an overall total influence for Goodwill (Y) of 85,53%. Then, there is an insignificant and positive influence of Human Capital (X1) on Capital Employed (Z1) by 3,63%. Then, there is a significant and positive influence of Human Capital (X1) and Capital Employed (Z2) on Structural Capital (Z2), with a large influence contribution of 98,99%.